2017
DOI: 10.1016/j.postharvbio.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of controlled atmosphere scheduling on strawberry and imported avocado fruit

Abstract: British grown strawberry cv. Sonata and Chilean avocado cv. Hass were exposed to controlled atmospheres (CA) of 15 kPa CO2 + 5 kPa O2 (5°C) and 10 kPa CO2 + 5 kPa O2 (5 or 20°C), respectively, at early, middle or late stages during postharvest storage of avocados and at early and middle stages for strawberries. Real-time respiration rate (RR) was measured during CA storage and regular fruit sampling carried out to assess disease severity, objective colour, ethylene production and firmness. The automated in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 25 publications
3
29
0
1
Order By: Relevance
“…The introduction of real-time respirometry has allowed the effects of CA to be monitored, reactivating research in this field. Previous studies have shown how targeted CA applications had a similar effect to continuous CA in extending shelf-life of onion, strawberry and avocado (Chope et al, 2007;Alamar et al, 2017). Based on these results, we hypothesized in this work that the graduated application of CA (GCA) could avoid this metabolic shock as it allows fresh produce to more slowly adapt to an optimal gaseous environment.…”
Section: Introductionmentioning
confidence: 89%
“…The introduction of real-time respirometry has allowed the effects of CA to be monitored, reactivating research in this field. Previous studies have shown how targeted CA applications had a similar effect to continuous CA in extending shelf-life of onion, strawberry and avocado (Chope et al, 2007;Alamar et al, 2017). Based on these results, we hypothesized in this work that the graduated application of CA (GCA) could avoid this metabolic shock as it allows fresh produce to more slowly adapt to an optimal gaseous environment.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, many postharvest techniques have been applied for reducing decay of strawberry fruit such as edible coating with Aloe vera and ascorbic acid [3], dipping in essential oils [4], melatonin treatment [5], controlled atmosphere storage [6], γ-irradiation [7], hot air and hot water dipping [2,8], Nano-ZnO treatment [9], pulsed light [10], and ethylene action inhibitor (1-MCP) treatment [11]. However, some of these treatments are not realistic due to low customer acceptance or high treatment price.…”
Section: Introductionmentioning
confidence: 99%
“…The early stage (postharvest storage) fruits exposed to CA, retained fruit firmness better however, it revealed a high incidence of internal discolouration after 7 days that means after the samples were withdrawn from the CA storage. At 5 • C, the avocado skin colour and flesh discolouration were maintained better by CA treatment compared to control fruit [39]. The CA reduced endogenous ethylene production, resulting in lighter, more vivid and firmer fruit, suggesting a reduction in senescence.…”
Section: Chilling Injury (Ci) and Pulp Spotmentioning
confidence: 91%
“…The effect of CA (10 kPa CO 2 + 5 kPa O 2 at 5 and 20 • C was investigated in avocados at different intervals for early, middle or late stages of postharvest storage [39]. Irrespective of timing, respiration rate of avocado stored at 20 • C was reduced while under CA environment ( Table 2).…”
Section: Chilling Injury (Ci) and Pulp Spotmentioning
confidence: 99%